2015
DOI: 10.1007/s11906-015-0570-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Central Nervous System Mechanisms in Resistant Hypertension

Abstract: Arterial hypertension remains a primary global health problem with significant impact on cardiovascular morbidity and mortality. The low rate of hypertension control and failure to achieve target blood pressure levels particularly among high-risk patients with resistant hypertension has triggered renewed interest in unravelling the underlying mechanisms to implement therapeutic approaches for better patient management. Here, we summarize the crucial role of neurogenic mechanisms in drug-resistant hypertension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Integrated neural, humoral, and renal mechanisms that collectively mediate increased renal Na ϩ retention and sympathetic nervous system activity have been implicated in the pathogenesis of hypertension (3,23,51,63). The importance of sympathetic nervous system alterations in human and experimental models of hypertension and associated mechanisms have been thoroughly previously reviewed (20,24,51). Of the factors that affect sympathetic activity, activity of the brain renin-angiotensin system (RAS) in cardiovascular regulatory nuclei is pivotal in the pathogenesis of hypertension in most animal models (2,21,69).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated neural, humoral, and renal mechanisms that collectively mediate increased renal Na ϩ retention and sympathetic nervous system activity have been implicated in the pathogenesis of hypertension (3,23,51,63). The importance of sympathetic nervous system alterations in human and experimental models of hypertension and associated mechanisms have been thoroughly previously reviewed (20,24,51). Of the factors that affect sympathetic activity, activity of the brain renin-angiotensin system (RAS) in cardiovascular regulatory nuclei is pivotal in the pathogenesis of hypertension in most animal models (2,21,69).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of studies in humans and animal models of hypertension, drugs and interventions can reduce BP and prolong survival rates by activating the parasympathetic nervous system (vagal), by blocking or inhibiting the SNS and the RAS ( 143 149 ). Early studies have shown that experimental lesioning of specific circumventricular organs of the forebrain, including the subfornical organ, the anteroventral third ventricle region involving the inferior aspects of the lateral terminalis, prevents the formation of several forms of experimental high BP ( 150 , 151 ). Increasing evidence indicates that the cardiovascular damage caused by overstimulation of the SNS and RAS, their α- and β-adrenergic receptors, and Ang II AT1 receptors is mediated through proinflammatory activation of the immune system ( 152 155 ).…”
Section: Potential Role Of the Thymus In Hypertensionmentioning
confidence: 99%
“…It is commonly thought that a chronic dysregulation of sympathetic outflow, i.e. neurogenic mechanisms based on neuroplasticity and a sensitization of the hypertensive response, may be major underlying causes of resistant hypertension [4,5]. Consequently, novel treatment approaches are needed, which target the chronic dysregulation of central blood pressure control.…”
Section: Is the At2r A Key To Treating Resistant Hypertension?mentioning
confidence: 99%
“…Neurogenic hypertension is not only characterized by sustained sympathoexcitation, but also by impaired baroreflex function [5]. As noted above, and shown in Figure 2, there is a high density of AT2R in the NTS, an area that has a major role in controlling baroreflex function [8,42].…”
Section: At2r and The Baroreflex Functionmentioning
confidence: 99%